The Baker pocket guide to world religions : what every Christian needs to know - McDermott, Gerald R. (Gerald Robert) (Grands Rapids, Mich. : Baker Books, 2008)
The Baker Pocket Guide to World Religions provides a short guide to help you grasp the central beliefs of those who belong to eight major religions of the world-dedicating full chapters to Islam, Hinduism, Judaism, Buddhism, Christianity, Confucianism and Daoism, and Shinto. Included in this fact-filled handbook are: personal testimonies from an adherent of each world religion, sketches of important world religious leaders of our day, sidebars explaining details of religious rituals and traditions, a helpful glossary of key terms, a chapter on how understanding world religions impacts Christian evangelism. - from publisher description.
Timeline: When did the religions start? -- Introduction: Why study the world religions? or, ignorance is not bliss -- Hinduisms : the world's oldest set of religions -- Judaism : Christianity's mother and older brother -- Buddhism : the west's favorite non-Christian religion -- Confucianism and Daoism : two of the biggest nation's three religions -- Christianity : what you believe but have a hard time explaining -- Shinto : the national religion of Japan -- Islam : the world's most important religion geopolitically -- Two common questions.
Includes bibliographical references (page 144).
Keywords: Religions